International students at community colleges: how are their needs being met? - Anayah, Bernadette, author; Kuk, Linda, advisor; Davies, Timothy, committee member; Kees, Nathalie, committee member; Young, Deborah, committee member (Colorado State University. Libraries, 2012)
An emerging trend today is the increased enrollment of international students at community colleges. International students look to American community colleges as a stepping stone to achieving an education that might otherwise be beyond their reach. They are attracted to the community college by the lower tuition costs, opportunities for guaranteed transfer to a four-year university, and the opportunity to study at a variety of geographical locations throughout the United States. California is one of the most popular destinations for international students in the United States. In 2011, more than 23,000 international students were enrolled in California's 112 community colleges. The purpose of this qualitative study was to examine the experience of international students at selected California community colleges and explore how they perceive their needs and expectations are being met. Twenty nine international students from 19 countries were interviewed at seven California community colleges with small, medium, and large international student programs. The phenomenological interview was used as the primary method of data collection. The interview questions were open-ended and allowed the participants to discuss the wide and varied nature of their experience as international students at community colleges. Through the use of an interpretive phenomenological approach to qualitative research, five thematic structures were identified: Reasons, Academic Experience, Social Experience, Cultural Experience, and Problems and Solutions. The essence of the phenomenon of the international student experience at the community college is identified as: The Stepping Stone.
Keywords: community college; international students; foreign students